Accessing the applicability of polarized protein‐specific charge in linear interaction energy analysis. Issue 9 (5th February 2014) - Jia, Xiangyu; Zeng, Juan; Zhang, John Z. H.; Mei, Ye
Abstract : The reliability of the linear interaction energy (LIE) depends on the atomic charge model used to delineate the Coulomb interaction between the ligand and its environment. In this work, the polarized protein‐specific charge (PPC) implementing a recently proposed fitting scheme has been examined in the LIE calculations of the binding affinities for avidin and β‐secretase binding complexes. This charge fitting scheme, termed delta restrained electrostatic potential, bypasses the prevalent numerical difficulty of rank deficiency in electrostatic‐potential‐based charge fitting methods via a dual‐step fitting strategy. A remarkable consistency between the predicted binding affinities and the experimental measurement has been observed. This work serves as a direct evidence of PPC's applicability in rational drug design. © 2014 Wiley Periodicals, Inc. Abstract : The applicability of a new polarized charge model, termed delta restrained electrostatic potential, in predicting the protein–ligand binding affinity is investigated. In this charge model, a perturbation term is added to the mean‐field library charge (e.g., AMBER charge) to capture the system dependence. Results from linear interaction energy studies of two systems show that this charge model can provide satisfactory binding free energies that are in high correlation with experimental measurements.